Mental healthcare services satisfaction and its associated factors among patients with mental disorders on follow-up in the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Melkam, Mamaru; Kassew, Tilahun (Frontiers in Psychiatry, 2023)
Background: Patient mental healthcare service satisfaction is a crucial component in evaluating the effectiveness and efficiency of clinical service delivery. It can be explained as the client's reaction to various aspects of the services they receive and their subjective assessment of the healthcare facilities and healthcare givers. Despite the importance of measuring mental healthcare service satisfaction few studies were conducted in Ethiopia. This study aimed to assess the prevalence of mental healthcare service satisfaction among patients with mental disorders who were on follow up in Northwest Ethiopia. Method: An institution-based cross-sectional study was conducted from June 1 to July 21 of 2022. All the study participants were interviewed on the follow-up visit consecutively. The Mental Healthcare Service Satisfaction Scale tool was used to measure patient satisfaction, Oslo-3 Social Support Scale, and other questionnaires were used. The data was checked for its completeness entered and coded using Epi-data version 4.6 the exported to Stata version-14 software for analysis. Bi-variable logistic and multi-variable regression analyses were employed to identify the factors significantly associated with satisfaction. AOR with 95% CI was used to report the result at a p-value of <0.05. Results: A total of 402 study participants were included in this study with a response rate of 99.7%. The overall mental healthcare service satisfaction was 65.46% with a 95% CI of (59.90,70.62). Not being admitted to psychiatry [AOR: 4.94; 95% CI (1.30, 8.76)], getting their drug inside the hospital [AOR: 1.34; 95% CI (3.58, 8.74)], and having strong social support [AOR:6.40; 95% CI (2.64,8.28)] were significantly associated with satisfaction. Conclusions: The prevalence of mental healthcare service satisfaction is very low therefore; more is expected to enhance the satisfaction of the patients who have to get the service from psychiatry clinics. The service delivered in the psychiatry unit must be increased to have good patient satisfaction which might be helpful for the improvement of the disorders.